An Inventory of Diagnostic Tools for Detection of COVID-19 - Bhatt, Akansha; Fatima, Zeeshan; Ruwali, Munindra; Hameed, Saif (Current Molecular Medicine, 2022)
The ongoing pandemic of coronavirus disease 2019 (COVID-19) caused by SARS-COV-2 has afflicted millions of lives globally and disrupted almost all the activities of mankind. Under such pressing circumstances when no effective therapeutics are available, a fast and accurate diagnosis of the coronavirus is the only way out to limit the transmission. Since the inception of COVID-19, the demand for diagnostic tests has increased day by day and RT-PCR is the commonly used screening test that is not only time-consuming but requires sophisticated resources. To address the increasing rate of spread of COVID-19, there is an urgent need for more diagnostic tools as the research on vaccines is still at a rudimentary level. This review summarizes an inventory of the diverse and currently available diagnostic methods based on nucleic acid and serology along with some of those working on novel principles viz. CRISPR, biosensors, and NGS. Additionally, accessible diagnostic kits that are already approved by the US and European authorities for the diagnosis of COVID-19 are also suggested that will help in selecting the most effective tests under the given scenario. Taken together, this review will pave way for further strengthening the research on the rapid and safer diagnostics of SARS-COV-2.
Keywords: COVID-19